The economic adjustment programme for Greece - Fifth review – October 2011 (Luxembourg, 2011)
"A joint Commission/ECB/IMF mission met with the Greek authorities in Athens from 21 August to 2 September and from 27 September to 11 October 2011. The mission assessed compliance by Greece with the terms and conditions of the fifth review under the economic adjustment programme and updated conditionality for the next reviews.